Dance and Drama in Aristotle's Dramatics (aka Poetics): New Principles from an Ancient Treatise. (2016) - Scott, Gregory
Abstract : In previous publications I demonstrated that dance and music are essential conditions in the definition of tragedy for Aristotle. This opens the door for a re-examination of the place of theatrical dance in the work usually considered to be the most influential treatise on drama in Western culture. Here I begin to explore how the principles of dance criticism might therefore now be developed, and I also discuss whether Aristotle modifies Plato's own critical principles pertaining to choral art (including dance) from Laws II.